Coupled effect of porous network and water content on the natural attenuation of diesel in unsaturated soils - An, Seongnam; Kibeum Kim; Woo, Heesoo; Yun, Seong-Taek; Chung, Jaeshik; Lee, Seunghak (Pergamon Press Ltd., 2022)
The natural attenuation potential of a vadose zone against diesel is critical for optimizing remedial actions and determining groundwater vulnerability to contamination. Here, diesel attenuation in unsaturated soils was systematically examined to develop a qualitative relationship between physical soil properties and the natural attenuation capacity of a vadose zone against diesel. The uniformity coefficient (C-u) and water saturation (S-w, %) were considered as the proxies reflecting the degree of effects by porous network and water content in different soils, respectively. These, in turn, are related to the primary diesel attenuation mechanisms of volatilization and biodegradation. The volatilization of diesel was inversely proportional to C-u and S-w, which could be attributed to effective pore channels facilitating gas transport. Conversely, biodegradation was highly proportional to C-u under unsaturated conditions (S-w = 35-71%), owing to nutrients typically associated with fine soil particles. The microbial community in unsaturated soils was affected by S-w rather than C-u. The overall diesel attenuation including volatilization and biodegradation was optimized at S-w = 35% for all tested soils.